Greek Political Imagery from Homer to Aristotle - Brock, Roger (Criminal Practice Ser, 2013)
FC -- Title -- Copyright -- Contents -- Conventions -- Acknowledgements -- Introduction -- 1 Gods as Kings, Kings as Gods -- 2 The State as a Household and Family -- 3 The Shepherd of the People -- 4 The Ship of State -- 5 The Body Politic -- 6 Leaders and Communities: The Archaic Period (c.750-480 BC) -- 7 Democracy and Autocracy: The Fifth Century (c.480-404 BC) -- 8 Orators and Philosophers: The Fourth Century to Alexander (c.400-322 BC) -- Epilogue -- Bibliography -- Index of Authors and Images -- Index locorum -- General Index.